A Validated RP-HPLC Method and Force Degradation Studies of Fexofenadine Hydrochloride in Pharmaceutical Dosage Form - Sanam, Sherejad; Nahar, Sharmin; Saqueeb, Nazmus; Rahman, SM Abdur (Dhaka University Journal of Pharmaceutical Sciences, 2018)
A stability indicating HPLC method was developed and validated for the quantitative determination of fexofenadine hydrochloride. An isocratic separation was achieved using phenomenex (C18) column (250×4.6 mm, 5 μm) with flow rate of 1.0 ml/min and UV detection at 254 nm. The mobile phase consists of 5Mm acetate buffer: acetonitrile (50:50; v/v) with pH 9.4 adjusted with acetic acid. The drug was subjected to oxidative, acidic, basic, neutral, photolytic and thermal degradation. All degradation products were eluted in an overall analytical run time of approximately 40 min with the parent compound fexofenadine hydrochloride at a flow rate of approximately 3.3±0.3 min. The method was linear over the concentration range of 31.5-500 μg/ml (r2 = 0.999) with limit of detection and quantification of 3.5 μg/ml and 10.1 μg/ml, respectively. The method has the requisite accuracy, selective, precision and robustness to assay fexofenadine HCl in tablets. Dhaka Univ. J. Pharm. Sci. 17(1): 43-50, 2018 (June)